TBC1D24 mutations- opening the DOORS to the associated syndromes - Szada-Borzyszkowski, Kacper; Owczarenko, Konstancja (Quality in Sport, 2026)
Introduction TBC1D24 mutations encompass a vast variety of very rare disorders, which can manifest in a wide array of manifestations. The phenotypes include the most common DOORS syndrome, as well as Developmental and Epileptic Encephalopathy with other epileptic syndromes, DFNB- Autosomal recessive nonsyndromic hearing loss and DFNA- Autosomal dominant nonsyndromic hearing loss. With the increasing availability of the genetic studies, there has been a steady increase in the cases reported in the literature, showing a growing increase in the importance of this mutation in developmental diseases. Aim To summarize current knowledge about the pathophysiology of the TBC1D24 mutations, clinical manifestations, their epidemiology, diagnosis and potential treatment of the patients with the focus on most common signs and symptoms. Material and methods A systematic literature review was conducted through PubMed database and Google Scholar, using the keywords “DOOR syndrome”, “DOORS syndrome”, “TBC1D24”, “Developmental and Epileptic Encephalopathy”, “DEE”, “Autosomal recessive nonsyndromic hearing loss”, “Autosomal dominant nonsyndromic hearing loss”, “DFNA” and “DFNB”.